ANALISIS PENGUKURAN KINERJA PERUSAHAAN DENGAN METODE PENDEKATAN BALANCED SCORECARD (Studi Kasus Pada Koperasi Simpan Pinjam (KSP) Lohjinawe Rembang) - awan febrianto (Jurnal Ilmu Administrasi Bisnis, 2016)
Performance measurement is used to determine the achievement of corporate objectives of the business unit performance by evaluating the achievement of results that have been achieved through the strategy set. Cooperative is an organization that puts the interests and welfare of members in the central position of the overall activities of cooperatives, in reality, many cooperatives in activities focused on financial factors, including KSP Lohjinawe Rembang. So that the customer and the employees a little neglected. Balanced Scorecard concept is here to help companies determine the extent to which the achievement of performance through four perspectives. This research is qualitative descriptive analysis. Source data used are primary data by questionnaire and in-depth interview to determine the assessment of the translation of the vision, mission and objectives of the company through target setting and weight to key performance indicator (KPI). Secondary data such as financial statements, the development of number of employees and branches of cooperatives in 2013-2015. Performance results are in a healthy position overall with a total score of 92.42 (standard wells 80 <x <100). Obtaining a score on four perspectives that are tailored to the weight of the Balanced Scorecard, financial perspective score was 55.32 (target 60), in the perspective of the customer (member) with a score of 18.25 (target 20), the internal business process perspective score was 10.42 ( target 10) and the last on learning and growth perspective score was 8.24 (target 10). The best performance was in the business process perspective that is able to exceed the target by the achievement of 104.19%. On the financial perspective and the customer perspective attainment results are equally amounted to 92.2%. While learning and growth perspective obtain the lowest achievement results with the percentage of 82.35%.